Overcoming the Barriers That Obscure the Interlinking and Analysis of Clinical Data Through Harmonization and Incremental Learning - Vasileios C. Pezoulas; Konstantina D. Kourou; Fanis Kalatzis; Themis P. Exarchos; Evi Zampeli; Saviana Gandolfo; Andreas Goules; Chiara Baldini; Fotini Skopouli; Salvatore De Vita; Athanasios G. Tzioufas; Dimitrios I. Fotiadis (IEEE Open Journal of Engineering in Medicine and Biology, 2020)
Goal: To present a framework for data sharing, curation, harmonization and federated data analytics to solve open issues in healthcare, such as, the development of robust disease prediction models. Methods: Data curation is applied to remove data inconsistencies. Lexical and semantic matching methods are used to align the structure of the heterogeneous, curated cohort data along with incremental learning algorithms including class imbalance handling and hyperparameter optimization to enable the development of disease prediction models. Results: The applicability of the framework is demonstrated in a case study of primary Sjögren's Syndrome, yielding harmonized data with increased quality and more than 85% agreement, along with lymphoma prediction models with more than 80% sensitivity and specificity. Conclusions: The framework provides data quality, harmonization and analytics workflows that can enhance the statistical power of heterogeneous clinical data and enables the development of robust models for disease prediction.